Maraging Steel

By optimizing chemical composition and process, martensite aging steel with high tempering resistance, toughness and dimensional stability are formed, which solves the problems of dimensional instability and polishing damage of existing steels at high temperatures, and improves the accuracy and life of the tool.

CN116457487BActive Publication Date: 2025-03-04UDDEHOLMS AB
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180074834.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-05
Filing Date
2021-11-04
Publication Date
2025-03-04
Estimated Expiration
2041-11-04

AI Technical Summary

Technical Problem

Existing martensite aging steels have problems of dimensional instability and polishing damage when used at high temperatures, and their highly reactive elements lead to unwanted transformations and hard inclusion formation, affecting the accuracy and life of the tool.

Method used

By optimizing chemical composition, limiting the content of elements such as carbon, silicon, nickel, molybdenum, and cobalt, increasing the content of chromium, and forming martensite aging steel with high tempering resistance, toughness and dimensional stability through gas atomization and heat treatment.

Benefits of technology

The dimensional stability and good polishing properties of steel at high temperatures are achieved, unwanted transformations and the formation of hard inclusions are reduced, and the accuracy and life of the tool are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116457487B_ABST
    Figure CN116457487B_ABST
Patent Text Reader

Abstract

The present invention relates to a maraging steel suitable for hot working tools, the steel consisting of the following in weight % (wt. %): C<0.08, Si 0.1-0.9, Mn<2, Cr 4.0-6.5, Ni 2.0-5.0, Mo 3.5-6.5, Co 2.0-5.5, Cu<4.0, Nb<0.1, V<0.1, Ti<0.1, Fe and impurities as the balance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] manual Technical Field

[0002] The present invention relates to novel maraging steels having properties suitable for use in tools, such as hot working tools and tools for plastics molding, and wherein the composition is also suitable for use in additive manufacturing methods. Background Art

[0003] The term "hot-work tool" applies to a large variety of tools used to work or shape metals at relatively high temperatures, such as tools for die casting, hot pressing, and molds for shaping plastics, as well as many other types of tools intended for use in work at high temperatures. Conventional hot-work tool steels are developed for strength and hardness during prolonged exposure to elevated temperatures, and generally use large amounts of carbide-forming alloys.

[0004] For hot working applications, different kinds of hot working tool steels are conventionally used, in particular 5% Cr steels such as H11 and H13. It is a high-quality hot working tool of this type. It is a high-performance chromium-molybdenum-vanadium steel produced by ESR. It contains a balanced carbon and vanadium content as described in WO9950468 A1. This type of steel uses particle strengthening (by precipitation of nano-sized carbides) to hinder dislocation movement, so-called secondary hardening steels.

[0005] It is also known to use maraging steels for hot working applications. Maraging steels are not hardened by carbon, but rather by precipitation of intermetallic phases in a highly alloyed matrix of low carbon martensite. Commercial maraging steels often contain 18% Ni and significant amounts of Mo, Co, Ti and Al. One of the most popular 18% Ni steels is 300 grade maraging steel, also known as 1.2709. A different class of maraging steels is stainless steel, and includes 17-7PH, 17-4PH, 15-5PH, PH15-7Mo, PH 14-8Mo and PH 13-8Mo.

[0006] Although maraging steels combine ultra-high strength and ductility, a disadvantage of maraging steels is that they contain high amounts of expensive alloying elements. A further disadvantage in many maraging steels is the partial reverse transformation from martensite to austenite that occurs during the aging treatment. This type of austenite is called reverse transformed austenite and is to be distinguished from retained austenite, which may also be present in maraging steels after hardening and aging. Since austenite and martensite have different densities, microstructural changes that occur during heat treatment and use result in transformed stresses and deformations. The transformation of austenite to martensite causes an increase in volume, and the transformation of austenite to martensite causes tool steel to shrink. Therefore, these unwanted transformations can lead to harmful dimensional changes, which is a problem in high-precision molds, tools and dies.

[0007] Furthermore, the presence of highly reactive elements can impair polishability due to the formation of hard inclusions such as Al2O3, TiN and VN.

[0008] Maraging steel metal powders have been increasingly used in additive manufacturing (AM) because the low carbon content helps prevent cracking during cooling. Due to the high cost of AM powders, recycling of the powders has gained considerable interest. However, AM powders will experience oxygen absorption during processing because the oxygen content in the selective laser melting (SLM) build chamber is generally on the order of 1000 ppm. Therefore, repeated heating of the powder during reuse can lead to significant oxygen uptake, especially if the steel contains large amounts of oxygen-active elements such as Al and Ti. Summary of the invention

[0009] The present invention aims to eliminate the above-mentioned disadvantages of previously known materials.

[0010] A general object of the present invention is to provide a new general purpose and economically viable maraging steel having improved properties for tools for hot working and plastic forming.

[0011] In particular, the present invention relates to steels having high tempering resistance combined with high toughness and high dimensional stability. Tempering resistance is the ability of steel to retain its hardness for a long time at elevated temperatures. Toughness is the ability of steel to absorb energy and deform plastically without breaking.

[0012] A further object is to provide a maraging steel having good polishability as well as good dimensional stability.

[0013] Another further object is to provide a maraging steel having a low content of reactive elements such that melt atomization of the steel can be performed by using nitrogen and the powder will have improved properties for use in recirculation in laser based AM.

[0014] The invention is defined in the claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Compared with steel, LOM has 200 times more Al nitrides and oxides.

[0016] Figure 2 The steel of the present invention has a LOM of 200 times. DETAILED DESCRIPTION

[0017] The importance of the individual elements of the claimed alloys and their interaction with each other as well as the limits of the chemical composition are briefly explained below. All percentages for the chemical composition of the steel are given in weight % (wt.%) throughout the description. The amounts of the phases are given in volume % (vol.%). The upper and lower limits of the individual elements can be freely combined within the limits set out in the claims.

[0018] The importance of the individual elements of the claimed alloys and their interaction with each other as well as the limits of the chemical composition are briefly explained below. All percentages for the chemical composition of the steel are given in weight % (wt.%) throughout the description. The upper and lower limits of the individual elements can be freely combined within the limits set out in the claims. For all values ​​given in this application, the arithmetic precision of the numerical values ​​may be increased by one or two places. Therefore, a value reported as 0.1% for example can also be expressed as 0.10 or 0.100%. The amounts of microstructural components are given in volume % (vol.%).

[0019] Carbon (≤0.08%)

[0020] Carbon is an undesirable impurity element in maraging steel. The upper limit of carbon is 0.08%. The upper limit can be set to 0.07, 0.06, 0.05, 0.04, 0.03 or 0.02%.

[0021] Silicon (0.1–0.9%)

[0022] Silicon is used for deoxidation. Si is also a strong ferrite former. Therefore Si is limited to 0.9%. The upper limit can be 0.8, 0.7, 0.6, 0.5 or 0.4%. The lower limit can be 0.1, 0.2 or 0.3%.

[0023] Manganese (≤2%)

[0024] Manganese helps improve the deoxidation and hardenability of steel. The content of Mn is not critical, but is limited to 2%. The upper limit can be set to 1.5, 1.0, 0.6, 0.5 or 0.4%.

[0025] Chromium (4.0–6.5%)

[0026] Chromium should be present in an amount of at least 4.0% to provide good hardenability and corrosion resistance. If the chromium content is too high, this can lead to the formation of undesirable phases such as delta ferrite. Therefore, the upper limit is 6.5%. The upper limit can be set to 6.0 or 5.5%. The lower limit can be set to 4.0, 4.1, 4.2, 4.3, 4.4 or 4.5%.

[0027] Nickel (2.0–5.0%)

[0028] Nickel is an austenite stabilizer that inhibits the formation of delta ferrite. Nickel gives the steel good hardenability and toughness. Ni promotes the precipitation of Mo as μ-phase. The lower limit may be 2.0, 2.5 or 3%. The upper limit may be 5.0, 4.5, 4.3, 4.1 or 4.0%.

[0029] Molybdenum (3.5–6.5%)

[0030] It is known that Mo in solid solution has a very favorable effect on hardenability. Mo is required for precipitation hardening during aging in the present invention. It appears that Mo forms the intermetallic μ-phase (Fe, Ni, Co)7Mo6 during aging. For this reason, the Mo content should be 3.5-6.5%. The lower limit may be 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4 or 4.5%. The upper limit may be or 6.4, 6.3, 6.2, 6.2, 6.0, 5.9, 5.8, 5.7, 5.6 or 5.5%.

[0031] Cobalt (2.0–5.5%)

[0032] Cobalt dissolves in the matrix of the maraging steel and reduces the solubility of molybdenum, so that Co promotes the precipitation of Mo as μ-phase.

[0033] In addition, Co increases M S Temperature and A c1 temperature, which leads to a reduced risk of forming reverse transformed austenite.

[0034] Copper (≤4%)

[0035] Cu may be optionally added to increase the strength of the steel by precipitation of ε-Cu. The upper limit is 4%, and may be set to 3.5, 3.0, 2.5, or 2.0%.

[0036] V, Nb, Ti, Al

[0037] V, Nb and Ti are strong carbide, nitride and / or oxide formers. Therefore, the content of these elements should be limited to avoid the formation of undesirable carbides and nitrides. Therefore, the maximum content of each of these elements is 0.1%. Preferably, these elements are limited to 0.05, 0.03, 0.02, 0.01 or 0.005. In particular, it is preferred to limit the content of Nb and Ti to impurity levels.

[0038] Impurity Elements

[0039] P and S are major impurities which may have a negative impact on the mechanical properties of the steel. Therefore, P may be limited to 0.1, 0.05, 0.04, 0.03, 0.02 or 0.01%.

[0040] If sulfur is not intentionally added, the impurity content of S can be limited to 0.05, 0.04, 0.003, 0.001, 0.0008, 0.0005 or even 0.0001%. However, to improve the machinability of the steel, S can be intentionally added in an amount up to 0.35%. The upper limit of S can be reduced to 0.30, 0.25, 0.15 or 0.10%.

[0041] The steel composition of the present invention consists of the following in weight % (wt.%):

[0042]

[0043] Fe and impurities are the balance.

[0044] The steel of the present invention is very stable against the formation of reversed austenite during heating. The martensite to austenite transformation temperature (A) of the steel of the present invention is c1 ) should preferably be above 680°C, which is a typical temperature for aluminum die casting. c1 It can be easily determined in a dilatometer and is taken as the temperature at which the thermal expansion first deviates from linearity. c1 The temperature is at least 690°C, preferably ≥ 700°C, more preferably ≥ 710°C and most preferably ≥ 720°C.

[0045] The steel preferably meets at least one of the following requirements:

[0046]

[0047]

[0048] And / or wherein the steel is in an aged condition and comprises intermetallic precipitates, wherein at least 50 volume % of the precipitates are of the (Fe,Ni,Co)7Mo6 type.

[0049] The steel more preferably meets at least one of the following composition requirements:

[0050]

[0051] and / or wherein the steel is in an aged condition and comprises intermetallic precipitates, wherein at least 70% by volume of the precipitates are of the (Fe,Ni,Co)7Mo6 type,

[0052] and / or wherein the cleanliness meets the following maximum requirements for fine residues in accordance with ASTM E45-97, Method A:

[0053] A A B B C C D D T H T H T H T H 1.0 0 1.5 1.0 0 0 1.5 1.0

[0054] According to a further preferred embodiment, the steel meets the following requirements:

[0055]

[0056]

[0057] According to another further preferred embodiment, the steel meets the following requirements:

[0058]

[0059] The alloy of the present invention may be in the form of a pre-alloyed powder produced by melt atomization, wherein the powder has a composition as described above.

[0060] The pre-alloyed powder may be produced by gas atomization, wherein at least 80% of the powder particles have a size in the range of 5 to 150 μm, and wherein the powder meets at least one of the following requirements:

[0061]

[0062] Where SPHT=4πA / P 2 , where A is the measured area covered by the particle projection, and P is the measured perimeter of the particle projection, and the sphericity (SPHT) is measured by Camsizer (morphology analyzer) according to ISO 9276-6, and where b is the shortest width of the particle projection, and l is the longest length.

[0063] The pre-alloyed powder particles preferably have a size distribution wherein at least 90% of the powder particles have a size in the range of 10 to 100 μm, and wherein the powder satisfies at least one of the following requirements:

[0064]

[0065]

[0066] The present invention also includes articles formed by additive manufacturing methods, wherein the articles include an alloy of the present invention alloy.

[0067] The alloy of the present invention can be used to produce hot working tools, tools for plastic molding and for small dies and any other tools. These products can be produced by any suitable method. The preferred production method is PM involving HIP or AM. In particular, due to the low reactivity of the alloy powder with oxygen and nitrogen, the steel powder is suitable for selective laser melting involving powder recirculation.

[0068] The alloys of the present invention can be produced by powder metallurgy (PM).

[0069] PM powders can be produced by conventional gas or water atomization of pre-alloyed steel.

[0070] If the powder is to be used for AM, gas atomization is the preferred atomization method, since it is important to use a technique that produces powder particles with a high degree of roundness and a low number of satellites. In particular, a close-coupled gas atomization method can be used for this purpose.

[0071] The powder particles for AM have a maximum size of 150 μm and preferably a size range of 10-100 μm with an average size of about 25-45 μm.

[0072] The most popular AM methods are liquid metal deposition (LMD), selective laser melting (SLM) and electron beam (EB) melting. Powder properties are also important for AM. According to ISO 4497, the powder size distribution measured by Camsizer should meet the following requirements (in μm):

[0073] 5≤D10≤35

[0074] 20≤D50≤55

[0075] D90≤80

[0076] Preferably, the powder should meet the following size requirements (in μm):

[0077] 10≤D10≤30

[0078] 25≤D50≤45

[0079] D90≤70

[0080] Even more preferably, the coarse fraction D90 is limited to ≤ 60 μm or even ≤ 55 μm.

[0081] The sphericity of the powder should be high. Sphericity (SPHT) can be measured by Camsizer and is defined in ISO 9276-6. SPHT = 4πA / P 2 , where A is the measured area covered by the particle projection and P is the measured perimeter of the particle projection. The average SPHT should be at least 0.80, and may preferably be at least 0.85, 0.90, 0.91, 0.92, 0.93, 0.94 or even 0.95. In addition, no more than 5% of the particles should have a SPHT of ≤0.70. Preferably, the value should be less than 0.70, 0.65, 0.55 or even 0.50. In addition to SPHT, aspect ratio can also be used for classification of powder particles. The aspect ratio is defined as b / l, where b is the shortest width of the particle projection and l is the longest length. The average aspect ratio should preferably be at least 0.85 or more preferably 0.86, 0.87, 0.88, 0.89 or 0.90.

[0082] Example 1

[0083] In this example, an alloy according to the invention is mixed with high-quality steel Uddeholm Make a comparison.

[0084] The alloy has the following nominal composition (in weight %):

[0085]

[0086] The steel of the present invention is formed by gas atomization and HIP. After cooling to room temperature (with a time of 600 s in the temperature range 800-500°C (t 8 / 5 =600s)), the steel was subjected to tempering twice at 605°C for 3 hours, which resulted in a hardness of 45HRC.

[0087] The comparative steel was conventionally produced by ingot casting followed by ESR. The remelted steel was subjected to austenitization in a vacuum furnace at 1020°C followed by gas quenching with a time of 600 s (t 8 / 5 =600s)). After cooling to room temperature, the comparative steel was subjected to tempering twice (2x2) at 615°C for 2 hours to obtain a hardness of 45HRC.

[0088] The alloy was then examined for its tempering resistance at a temperature of 600° C. The results are given in Table 1.

[0089] Table 1. Tempering resistance at 600° C. Hardness (HRC) as a function of time.

[0090]

[0091] Furthermore, the toughness of the steel was examined after tempering, and it was found that the steel of the present invention had a Charpy-V (Simply Supported Beam-V Notch) toughness of 25 J, while the comparative steel had a Charpy-V toughness of 22 J. Therefore, it can be seen that the steel of the present invention has much higher tempering resistance than the comparative steel.

[0092] The microstructure of the steel was examined after aging, and it was found that the precipitates that caused hardening in the steel of the present invention were (Fe, Ni, Co)7Mo6, i.e., intermetallic μ-phases. Precipitation Module (TC-Prisma, Thermo Calc Version 2021b) was used as a calculation tool for simulating the precipitation process in the steel of the present invention. The results of the precipitation calculations for the steel of the present invention used in this example show that the size of the intermetallic μ-phase will be about 20 nm after 10 hours, and the amount of μ-phase will be slightly less than 5 volume %.

[0093] Example 2

[0094] In this example, an alloy according to the invention is compared with a 300 grade maraging steel (1.2709).

[0095] The alloy has the following nominal composition (in weight %):

[0096]

[0097] Gas atomized powders of these alloys were subjected to selective laser melting (SLM) in an EOS M290 system.

[0098] It was found that the steel according to the invention contained no retained austenite in the finished condition (<2% by volume), whereas the comparative steel contained 11% by volume of retained austenite. The amount of retained austenite was determined by X-ray diffraction according to standard ASTM E975-13.

[0099] The tendency to form reversed austenite during aging was examined by keeping the steel at an aging temperature of 540° C. for 1 hour. The examination showed that the steel according to the invention did not form any reversed austenite, while the amount of austenite in the comparative steel increased to 17% by volume. Thus, aging for the comparative steel 1.2709 was carried out at the martensite to austenite transformation temperature (A c1 ) The thermal expansion of steel 1.2709 will therefore be influenced by the martensite to austenite transformation during reheating.

[0100] The absence of a martensite to austenite transformation in the steel according to the invention appears to be caused by an austenite transformation start temperature above the aging temperature. This was verified by examination in a dilatometer, which showed that the A c1 The temperature is 730℃ and Ac3 The temperature is 925°C. Therefore, the reheating temperature is c1 The reverse transformation austenite is not formed during the temperature period. It can be seen from this that the steel of the present invention can be used for die casting of aluminum, which is generally carried out with a melt temperature of about 680°C.

[0101] The microstructure of the steel was examined after aging and it was found that the precipitations causing hardening in the steel of the present invention were (Fe,Ni,Co)7Mo6, ie, intermetallic μ-phases.

[0102] As expected, the precipitations causing hardening in the comparative steel 1.2709 are (Fe,Ni,Co)3(Ti,Mo) as expected, and only small amounts of μ-phase are found.

[0103] Example 3

[0104] The susceptibility to the formation of non-metallic inclusions when subjected to an atmosphere containing oxygen was qualitatively examined. A steel according to the invention having the same composition as in Example 2 was compared to the steel Uddeholm For comparison, the nominal composition of the comparative steel was 0.03% C, 0.3% Si, 0.3% Mn, 12.0% Cr, 9.2% Ni, 1.4% Mo and 1.6% Al.

[0105] Both steels were subjected to melting in an HF furnace under a protective argon atmosphere and the melt was subsequently cast in inclined copper troughs in the open air.

[0106] The same sample was taken and examined in LOM at 200x magnification. Figure 1 and Figure 2 As shown in , and the comparison shows, the sensitivity of the steel of the present invention to oxygen is much lower than that of the comparative steel.

[0107] Industrial Applicability

[0108] The alloys of the present invention are useful in a wide range of applications. In particular, the alloys are useful in tools and dies for hot working and plastic forming and for AM applications.

Claims

1. A steel suitable for hot working tools, said steel consisting, in wt. %, of: Fe and impurities are the remainder, The transformation temperature from martensite to austenite is A c1 Above 680℃, wherein the steel is in an aged condition and comprises intermetallic precipitates, wherein at least 50% by volume of the precipitates are of the (Fe,Ni,Co)7Mo6 type, and wherein the cleanliness meets the following maximum requirements for fine residues according to ASTM E45-97, Method A: 。 2. The steel according to claim 1, which meets at least one of the following requirements:

3. The steel according to claim 1 or 2, which meets at least one of the following composition requirements: and / or the transformation temperature A from martensite to austenite c1 Above 700℃, And / or wherein the steel is in an aged condition and comprises intermetallic precipitates, wherein at least 70 volume % of the precipitates are of the (Fe,Ni,Co)7Mo6 type.

4. The steel according to claim 1 or 2, which meets the following requirements: And, optionally, wherein the martensite to austenite transformation temperature A c1 Above 710℃.

5. The steel according to claim 1 or 2, which meets the following requirements: And, optionally, wherein the martensite to austenite transformation temperature A c1 Above 720℃.

6. Pre-alloyed powder produced by melt atomization, wherein the pre-alloyed powder has the composition of the steel according to any one of claims 1 to 5.

7. The prealloyed powder according to claim 6, wherein the prealloyed powder is produced by gas atomization, at least 80% of the powder particles have a size in the range of 5 to 150 μm, and wherein the prealloyed powder meets at least one of the following requirements: Powder size distribution, in μm: 5≤D10≤35 20≤D50≤55 D90≤80 Average sphericity, SPHT ≥ 0.85 Average aspect ratio, b / l ≥ 0.85 Where SPHT=4πA / P 2 , where A is the measured area covered by the particle projection, and P is the measured perimeter of the particle projection, and the sphericity is measured by a morphology analyzer according to ISO 9276-6, and where b is the shortest width of the particle projection, and l is the longest length.

8. The prealloyed powder according to claim 6, wherein at least 90% of the powder particles have a size in the range of 10 to 100 μm, and wherein the prealloyed powder meets at least one of the following requirements: Powder size distribution, in μm: 10≤D10≤30 25≤D50≤45 D90≤70 Average sphericity, SPHT ≥ 0.90 Average aspect ratio, b / l ≥ 0.88 Where SPHT=4πA / P 2 , where A is the measured area covered by the particle projection, and P is the measured perimeter of the particle projection, and the sphericity is measured by a morphology analyzer according to ISO 9276-6, and where b is the shortest width of the particle projection, and l is the longest length.

9. An article formed by an additive manufacturing process, wherein the article comprises the steel according to any one of claims 1 to 5.

10. Use of the steel according to any one of claims 1 to 5 for producing tools for hot working.

11. The use according to claim 10, wherein the tool is a die.

Citation Information

Patent Citations

  • Steel material for hot work tools

    WO1999050468A1

  • Steel suitable for hot working tools

    CN111183241A

  • Large steel forging - of high strength,ductility and machinability

    DE2141026A1